An Introduction to Rule-Based Feature and Object Perception for Middle School Students - DiPaola, Daniella; Malachowsky, Parker; Blair Black, Nancye; Alghowinem, Sharifa; Du, Xiaoxue; Breazeal, Cynthia (Proceedings of the AAAI Conference on Artificial Intelligence, 2024)
The Feature Detection tool is a web-based activity that allows students to detect features in images and build their own rule-based classification algorithms. In this paper, we introduce the tool and share how it is incorporated into two, 45-minute lessons. The objective of the first lesson is to introduce students to the concept of feature detection, or how a computer can break down visual input into lower-level features. The second lesson aims to show students how these lower-level features can be incorporated into rule-based models to classify higher-order objects. We discuss how this tool can be used as a "first step" to the more complex concept ideas of data representation and neural networks.